The First-Pass Isolation Effect in High-Power Short-Duration Compared to Low-Power Long-Duration Atrial Fibrillation Ablation: a Predictor of Success - Vassallo, Fabricio; Meigre, Lucas Luis; Serpa, Eduardo; Lovatto, Carlos; Cunha, Christiano; Carloni, Hermes; Simoes Jr., Aloyr Simoes Jr.; Meira, Karla; Pezzin, Flávia; Lacerda Jr., Orly; et al. (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Introduction: Different results are described after atrial fibrillation ablation and multiples predictors of recurrence are well established. Objective: Evaluate and analyze if first-pass isolation effect (FPI) during first atrial fibrillation (AF) ablation with high-power short-duration (HPSD) comparing to low-power long-duration (LPLD) can impact on late outcome. Methods: Observational, retrospective study, 144 patients submitted to HPSD and LPLD ablation. HPSD: 71 patients, 50 (70.42%) males, mean age 59.73 years, 52 (73.24%) hypertension, 44 (61.97%) obstructive apnea, 23 (32.39%) arterial disease, 20 (28.17%) diabetes, and 10(14.08%) stroke. CHADS2VASC2 2.57. CT: 73 patients, 50 (68.49%) males, mean age 60.7 years, 53 (72.60%) hypertension, 41 (56.16%) obstructive apnea, 28 (38.36%) arterial disease, 14 (19.17%) diabetes and 8 (10.96%) stroke. CHAD2SVASC2 2.22. Results: Recurrence occurred in 33 patients (22.92%) at 12 months follow-up, HPSD with 9 patients and LPLD with 24 patients. Higher rate of bilateral FPI were observed in HPSD patients with 62 of 71 patients comparing to 17 of 73 patients in LPLD (P < 0.00001). At the end of study 62 (87.32%) of 71 HPSD patients were in sinus rhythm comparing to 49 (67.12%) of 73 patients in LPLD (P 0.0039). Conclusion: HPSD ablation produced higher rates of FPI comparing to LPLD. HPSD compared to LPLD showed a superiority in maintaining sinus rhythm at 12 months. At patients submitted to HPSD protocol ablation, FPI could predict higher rate of sinus rhythm at 12 months follow-up.